Quantification of Amylase Lipase and Protease in the Digestive Tract of Japanese Quail - Beena V (Department of Physiology and Biochemistry, College of Veterinary and Animal Sciences, 1997)
Japanese quails, being the most recently introduced species of poultry in India, are the least studied among the different domestic species of birds. For economic rearing of these valuable birds a thorough understanding of their basic digestive processes is essential. Keeping this point in view an attempt; was made to study the digestive physiology of adult Japanese quails (Coturnix coturnix japonica) especially the quantification of digestive enzymes like amylase, protease (pepsin) and lipase of different regions of digestive tract, the determination of pH of the contents of crop, proventriculus, gizzard and small intestine and the feed passage rate (FPR). One hundred and ninety two, six-week old Japanese quails of the same strain (egg type) were selected, at random, from the Kerala Agricultural University Poultry Farm, Mannuthy and maintained on standard, identical managemental and feeding conditions in cage system for a period of two weeks in order to stabilize the experimental conditions in the Department of Physiology and Biochemistry, College of Veterinary and Animal Sciences, Mannuthy. A batch of 24 birds (12 males and 12 females) of the same hatch were subjected for the quantification of the specific digestive enzyme in a particular region of the digestive system. Seven batches of